Modeling and Simulation of Organic Rankine Cycle (ORC) for Power Generation - Soon , Yung Wang (IRC, 2016)
Organic Rankine Cycle (ORC) has becoming a trend in the power generation sector as it is capable to employ low quality of heat source in order to produce high amount of energy. In fact, there are several researches which are conducted to determine the best working fluids for ORC. As the working fluids for ORC are normally flammable, it is suggested to mix with refrigerant to lower the flammability risk of the fluids. Thus, the objective of this research is to find out the best working fluid among the selection of benzene, pyridine, and thiophene as well as the zeotropic mixture with refrigerant HCF-134a for ORC which uses waste heat from manufacturing industries as its heat source. With the purpose of this research, several scopes of study are developed for the betterment of the result of the research. These include the development of the thermodynamic profile and simulation by using Aspen HYSYS version 8.